Estimating patterns in the under-reporting of suicide deaths in India: comparison of administrative data and Global Burden of Disease Study estimates, 2005–2015. Issue 6 (30th November 2020) - Arya, Vikas; Page, Andrew; Armstrong, Gregory; Kumar, G Anil; Dandona, Rakhi
Abstract : Background: It has been proposed that the National Crime Records Bureau (NCRB), which reports suicides in India, differentially underenumerates suicides by geographic and demographic factors. We assessed the extent of potential underenumeration by comparing suicides recorded in NCRB data with recent estimates of Indian suicides developed by the Global Burden of Disease (GBD) initiative. Methods: Age-standardised suicide rates were calculated for both data sources by sex, age and state, and rate ratios of NCRB to GBD estimates by corresponding strata were compared to ascertain the relative under-reporting in the NCRB report. Results: The GBD Study reported an additional 802 684 deaths by suicide (333 558 male and 469 126 female suicide deaths) compared with the NCRB report between 2005 and 2015. Among males, the average under-reporting was 27% (range 21%–31%) per year, and among females, the average under-reporting was 50% (range 47%–54%) per year. Under-reporting was more evident among younger (15–29 years) and older age groups (≥60 years) compared with middle age groups. Indian states belonging to low Socio-Demographic Index (SDI) generally had greater underenumeration compared with middle and high-SDI states. Conclusion: NCRB data under-report suicides in India, and differentially by sex, age and geographic area, possibly because of lack of community-level reporting of suicides due to social stigma and legal consequences. While the recent decriminalisation of suicide is expected to improve community-level reporting of suicides, suicide prevention policies should be developed, with a priority to address social stigma attached with suicide and suicidal behaviour, especially among females.